Metode Pembiasaan Sebagai Upaya Internalisasi Nilai - Nilai Ajaran Islam Di SMP Muhammadiyah 5 Surakarta Tahun Pelajaran 2015/2016 - Azhani, Riggina; , Dra. Chusniatun, M.Ag; , Drs. Zaenal Abidin, M.Pd (2017)
Habituation method is a form of activity that repetates the same things. This repetition is deliberately done so many times in order to associate the stimulus with a response to be very strong or in other words not easily forgotten. In education, process of internalizing the values of Islam, has to be considered by students to be able to practice and obey the teachings and values of Islam in their lives, both habluminallah and habluminanas. So the purposes of Islamic religious education achieve. SMP Muhammadiyah 5 Surakarta as an educational institution based on religion of Islam tries to create religious atmosphere in the school environment through the activities and religious practices are carried out routinely and programmed and expected to transform and internalize the value of the teachings of Islam as well to students. Formulation of the issue in this research ishow is the implementation of the method of habituation as an attempt to internalize the values of Islam and What are the values internalized in self students?.Based on this background, the purpose of this study is to describe the implementation of the conditioning methods in an attemp to internalize the values of Islam to learners. This research is a field one research activities carried out in a particular community by visiting the direct target object. The method used in this study is the observation, documentation and interview. Whereas data analysis is done by descriptive method. Of the results of this study concluded that if the students familiarized doing somthing repeatedly and consistently then the values of Islamic teachings should be more easily internalized by students. Data obtained states that students who are initially forced lng become accustomed to and love do good conduct or behaviors. All students indicate a postive behavioral change towards the use of such methods. Therefore the internalization of Islamic teachings anda values by habituation method is very effective method.